Determination of Characteristic Impedance in a Retrospective Cohort of Coronary Artery Disease in South Africa - Els, Danelle (University of the Witwatersrand, Johannesburg, 2024)
The relationship between coronary artery disease (CAD) and proximal aortic stiffness-induced increases in central arterial forward wave pressures (Pf) is uncertain. Using central pressure and aortic velocity and diameter measurements, we compared aortic characteristic impedance (Zc) (n=71) and central arterial pressure wave morphology (n=189) in patients with CAD to central arterial function in 210 age- and sex-matched controls from a community study. The results showed that Zc was markedly increased in patients with CAD compared to community controls (p<0.0001). In addition, after adjustment for mean arterial pressure and aortic root diameter, the early systolic pressures generated by the product of peak aortic flow (Q) and Zc (PQxZc) and Pf were markedly increased in patients with CAD as compared to controls (p<0.0001). This increase in Pf was accounted for by an enhanced PQxZc at peak PPc rather than increases in re-reflected wave pressures. Further adjustments for either brachial PP or systolic blood pressure (SBP) showed that higher Pf values were retained in the CAD patients (p<0.05, p<0.01, p<0.0001). After adjusting for conventional risk factors, peak central aortic PPc was higher in patients with CAD as compared to controls (p<0.05, p<0.005, p<0.0001). However, after adjusting for brachial SBP and confounders, central aortic PPc did not differ between the groups. Thus, increases in stiffness-associated proximal aortic Zc in patients with CAD translate into marked increases in Pf, but not peak PPc beyond brachial BP. These findings suggest that pulsatile load responsible for CAD is beyond brachial BP and poorly indexed by peak PPc.
A research report submitted in fulfillment of the requirements for the Master of Science in Medicine, in the Faculty of Health Sciences, School of Physiology, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; coronary artery disease (CAD); characteristic impedance (Zc) (n=71); SDG-3: Good health and well-being